Exploring the Feasibility of Using Commercially Available Vertically Pointing Wind Profiling Lidars to Acquire Thunderstorm Wind Profiles - Gunter, William Scott (Frontiers in Built Environment, 2019)
While multiple types of remote sensing instruments have been used to investigate wind profiles associated with thunderstorms, the use of profiling Lidars (LIght Detection And Ranging) has been mostly limited to the wind energy sector. Using data from a wind energy company, this study explores the feasibility of profiling lidar data to obtain low-level (<150 m) wind profile information in and near thunderstorms. Two case studies were analyzed in which strong thunderstorms passed over the lidar while the remote sensor was operational and collecting wind speed, wind direction, and vertical velocity profiles at sub-minute resolution. Wind time histories at different levels of the wind profiles revealed that the lidar was able to collect data through the entirety of each event. The time histories also displayed a very typical thunderstorm outflow wind structure that has frequently been observed with in situ anemometry and radar remote sensing. As expected, vertical velocity data were mostly negative (indicating downdraft) during both events and exceeded – 6 m s-1 in one event. A comparison of the lidar data with in situ sonic and cup anemometers was also performed. While only 10-minute anemometer data were available, the limited comparison suggested a high degree of similarity in the mean sense, but standard deviations associated with the 10-minute lidar data were much lower than those of the anemometer data. Though this latter result was not entirely unexpected, it serves to demonstrate some of the issues that should be addressed prior to using profiling lidars in thunderstorms.